To What Extent Trust In Leader And Ethical Climate Affect Turnover Intention? A Research On Private And Public Bank Employees - (:unkn) unknown (ARDABIL INDUSTRIAL MANAGEMENT INST, 2018)
Drawing on theory and research, the mediating roles of trust in leader and ethical climate on the relations between ethical leadership, organisational justice, and turnover intention are examined with structural equation modelling. Using 571 private and 535 public bank employees, it is found that turnover intention can be decreased by increasing trust in leader and ethical climate in the environment. In addition, the full mediations of trust in leader and ethical climate are supported in the relations between ethical leadership and turnover. However, trust in leader and ethical climate are found to have partial mediating effects between distributive justice and turnover and it is also found that procedural justice does not have an effect on turnover intention. Moreover, invariance tests have identified both model and structural invariance indicating equivalence across both private and public bank samples. (C) AIMI Journals
Keywords: Ethical Climate; Ethical Leadership; Organisational Justice; Private and Public Banks; Structural Equation Modelling; Trust in Leader; Turnover Intention; ORGANIZATIONAL JUSTICE; PROCEDURAL JUSTICE; JOB-SATISFACTION; SOCIAL-EXCHANGE; MEDIATING ROLE; DISTRIBUTIVE JUSTICE; COMMITMENT; BEHAVIOR; OUTCOMES; MANAGER